Rethinking Activism and Expertise within Environmental Health Conflicts - Arancibia, Florencia Paula (2016)
This review presents the contributions of research on the intersection of science and social movements, its theoretical and methodological limitations, and potential solutions for its further development. Three different types of relationships between activism and knowledge have been identified within environmental health conf licts: (i) lay – activists requesting help from sympathetic scientists in order to conduct independent studies; (ii) expert – activists promoting new research agendas and sub-fields within established scientific disciplines; and (iii) expert – activists acting beyond the limits of the academic community and partnering with social movements. In this review, I argue that much of the existing literature considers expertise as “something” possessed by individuals, and heavily emphasizes the difference between “lay” and “expert” activists. This entails two main theoretical reductionisms: (i) reification of knowledge; and (ii) overlooking the contribution of activism to expertise and vice versa. I propose considering expertise as the property of a network and focusing future research within environmental health conf licts on the co-emergence and construction of a network of expertise (Eyal 2013) or ethno-epistemic assemblage (Irwin & Michael 2003) and social movements. Through this symmetrical network approach, we will be able to develop a more consistent theory of the co-production of activism and expertise, as well as its political implication to fight environmental health injustice.